(untitled) (Indonesian Health Justice Review, 2025)
Mental health remains one of the most neglected aspects of Indonesia’s healthcare system, with significant legal, social, and cultural barriers preventing access to care. This paper explores the legal and policy challenges that hinder mental health care access, particularly for marginalized populations, such as low-income individuals, women, and rural residents. Using a combination of policy analysis, interviews with mental health professionals, and case studies, the research identifies the gaps in mental health legislation, the stigma surrounding mental illness, and the insufficient allocation of resources for mental health services. Findings suggest that Indonesia’s mental health care system is underfunded, lacks proper infrastructure, and is constrained by outdated laws and practices. Mental health services are often seen as secondary to physical health, and there is a significant lack of trained professionals, particularly in rural areas. The paper argues that mental health care is an essential component of health justice and that addressing the social determinants of mental health—such as poverty, gender inequality, and social exclusion—is critical for achieving equitable healthcare for all. Recommendations include the expansion of mental health services, comprehensive reform of mental health laws, and increased public awareness to reduce stigma and promote mental well-being as part of the broader health agenda.